Decision Support System On Court Judge Lubukpakam Method Using SAW (Simple Additive weighting) - Saragih, Diana Sari Muliani; Hasugian, Penda Sudarto (Information Technology and Science (ITScience), 2020)
In the legal world, especially in trials that took place in the Court, the law is the most important system in the implementation of a series of institutional strength.The cornerstone of judicial justice in Indonesia is based on Pancasila and the human dignity and the protection of human rights guarantees contained in Law No. 8 In 1981 the Code of Criminal Procedure (Criminal Procedure Code).Various studies have been conducted to assist in the termination of a case, as is done by Rumodar RF et al (2016) on the use of one of the MADM method, namely Simple Additive weighting. The analysis result is a system that can display information on article associated with a form of crime that is done that ensnared or incriminate the perpetrator, the system will also feature a sanction that is given of each chapter are violated.